Implementation and evaluation of a 'Navigator' role to improve emergency department throughput. Issue 3 (August 2017) - Fulbrook, Paul; Jessup, Melanie; Kinnear, Frances
Abstract: Background: Emergency department overcrowding impacts patients, staff, and quality of care, and there is government pressure to optimize throughput and reduce waiting times. One solution for improving patient flow is the emerging 'navigator' role: a nurse that supports staff in care delivery; facilitating efficient and timely patient movement through the emergency department. Methods: A 20-week project was implemented to evaluate an emergency department nurse navigator role. A controlled trial was used. The navigator worked on a week-on-week-off basis, eight hours per day, seven days per week. Time-based and cost-associated outcomes were compared. Results: Data from nearly 20, 000 presentations during the trial period were analysed. All outcomes were improved during the ten weeks the Navigator was working. A slight improvement in National Emergency Access Target compliance was shown, with an average of 4.5 min per presentation saved. The labour cost associated with the time saved was estimated to be $170, 000. Conclusions: The results from this study indicate that for a relatively small investment, complementary nursing roles such as the navigator can impact emergency department patient flow. However, further studies are required to determine optimisation of the role. Relevance to practice: This study provides rigorous evidence of the effects of a nurse navigator role on emergency department throughput. Whilst positive outcomes were demonstrated, suggesting a whole-of-system benefit, the magnitude of effect on a per-presentation basis was relatively small. Further studies are required to demonstrate the clinical relevance of such roles.